Co-action between physical activity and fruit and vegetable intake in racially diverse, obese adults - Heredia, Natalia I. (Am J Health Promot, 2019)
PURPOSE. There is minimal understanding of the potential for coaction, defined as action on one behavior increasing the likelihood of taking action on another behavior, between physical activity (PA) and fruit and vegetable (FV) intake. The purpose of this study was to assess the bidirectional coaction between FV intake and PA, as well as self-efficacy for these behaviors, in a racially diverse sample of obese adults. DESIGN. This is a secondary analysis using data collected from the Path to Health study, a randomized controlled trial. ClinicalTrials.gov Identifier: . SAMPLE. Obese adults who completed baseline and 6 month follow-up assessments. MEASURES. For this study, data on FV intake, leisure-time PA, and seven-day accelerometer data were analyzed at baseline and 6-month follow-up. ANALYSIS. We interchanged modeling the FV intake and PA change variables as the independent and dependent variables. Multiple imputations were conducted; linear and multinomial regression models. RESULTS. The sample (n=168) was 59% female and mainly split between white (42%) and African American (42%). Change in self-efficacy for PA was predictive of change in self-efficacy for FV intake, and vice versa. As compared to participants with no change in FV intake, someone with a positive change in FV intake was more likely to have a positive change in self-reported PA (Adjusted RR=6.72, 95% CI 1.69–26.68). Likewise, as compared to no change, participants with a positive change in self-reported PA were more likely to report a positive change in FV intake (Adjusted RR=6.79, 95% CI 1.70–27.17). CONCLUSION. Findings suggest coaction between self-efficacy for FV intake and PA, as well as between FV intake and PA. Coaction could be capitalized on to more effectively promote both energy-balance behaviors.